FUNGSI LEGISLASI DEWAN PERWAKILAN RAKYAT DAERAH DALAM PELAKSANAAN OTONOMI DAEARAH KABUPATEN KEPULAUAN SANGIHE - GALANGBULAENG, VERAWATI OLIVIA; Rumapea, Patar; Kolondam, Helly (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRAKDRPD is one of the main pillars to support the regional administration. Furthermore, in an effort to realize their tasks and functions, Parliament has a role in terms of creating transparency in local governance.Pleased with this, since decentralization, Parliament as one of the elements of regional government, is increasingly playing the role and authority as well as an institutional bridge between the aspirations of citizens of diverse with political decisions development that translate these aspirations into formats payments area along the eye budget.Authority in the legislative process, budgeting and supervision of the regional administration of making Parliament can play a major role in the making of public policies in the area. With such authority allows Parliament take a role in determining local regulations, budgets and public services to be more pro-people. Keywords: Functions Legislation, Regional Representatives Council